Potential of exo-polysaccharide producing plant growth promoting bacteria in growth promotion and disease suppression of chilli - Jinisha, B J P; Chitra, N; Soumya, V I; Anu, R S; Anith, K N (Plant Science Today, 2025)
Bacteria producing exo-polysaccharides (EPS), isolated from the rhizosphere of chilli (Capsicum annuum L.), demonstrate considerable potential for enhancing plant growth and managing fungal pathogens. These bacteria exhibit a variety of plant growth-promoting traits, including the synthesis of phytohormones like indole-3-acetic acid (IAA) and gibberellic acid (GA), as well as the production of siderophores, phosphate solubilization and ammonia release. The antagonistic activity of these isolates against chilli anthracnose pathogen Colletotrichum capsici, was evaluated using dual plate assay. Among the isolates tested, Bacillus halotolerans CAJPH6 showed the maximum inhibition of C. capsici (72 %), followed by Bacillus stercoris CAJRH6 (70 %) and Bacillus subtilis CFORH5 (64 %). The gravimetric evaluation of EPS production showed that Bacillus stercoris CAJRH6 yielded 0.93 mg mL-1, Bacillus subtilis CFORH5 produced 0.89 mg mL-1 and Bacillus halotolerans CAJPH6 generated 0.72 mg mL-1. This study emphasizes the potential of EPS-producing bacterial isolates as an alternative to chemical fertilizers and fungicides, supporting sustainable and eco-friendly farming practices.